Design Optimization of MEMS Based Piezoelectric Energy Harvester For Low-Frequency Applications - Singh, Roohi (My University, 2018)
In recent years, piezoelectric based energy harvester had become major research topic. Piezoelectric materials are excellent transducers in converting vibrational energy into electrical energy, and vibration based piezoelectric generators are seen as an enabling technology for wireless sensor networks, especially in self powered devices. These are mostly made of thin film technology and different configurations as unimorph and bimorph for sensor and actuator applications. In this thesis work, analysis and comparison of two widely used cantilever design in MEMS energy harvesting devices i.e. wide beam structure and narrow beam structure have been done. Aluminum Nitride (AIN) is chosen as a piezoelectric material due to its CMOS and biocompatibility. To study the output of the design, Finite Element Modelling was used. The power density obtained based on the volume of the structure was 14.8 μW/cm3 for the wide beam structure and 0.10 μW/cm3 for narrow beam structure individually. In selecting a device, bandwidth is also a vital parameter. An array of cantilever structure resulted in a bandwidth of 4 Hz for the wide beam structure and 8.1 Hz for narrow beam structure respectively. The conclusion of the results are wide beam structure is preferred to increase power density and a narrow beam for the wide bandwidth. High power density also has a disadvantage which is likely to fail where acceleration is high, as due to increasing stress which they experience.
Keywords: Energy harvesting; Micro-Electro-Mechanical System; (MEMS), P; Aluminum Nitride (AIN); Finite Element Modeling (FEM); iezoelectric unimorph